Psychomotor Intervention in Elderly Patients with respiratory changes: Chronic Obstructive Pulmonary Disease - Maria Santos, Rafaela Moreira (2019)
When it comes to aging we must take into account not only chronological age, but also a complex and dynamic process of biological, psychological and social changes. COPD (respiratory alteration) is highlighted in this study, for being one of the most common diseases and one of the main causes of worldwide mortality in the elderly. Therefore a psychomotor and social-emotional intervention is proposed, in order to promote the quality of life of the elderly.